2017
DOI: 10.1021/acs.jmedchem.7b00572
|View full text |Cite
|
Sign up to set email alerts
|

Structure Based Design of N-(3-((1H-Pyrazolo[3,4-b]pyridin-5-yl)ethynyl)benzenesulfonamides as Selective Leucine-Zipper and Sterile-α Motif Kinase (ZAK) Inhibitors

Abstract: A series of N-(3-((1H-pyrazolo[3,4-b]pyridin-5-yl)ethynyl)benzenesulfonamides were designed as the first class of highly selective ZAK inhibitors. The representative compound 3h strongly inhibits the kinase activity of ZAK with an IC of 3.3 nM and dose-dependently suppresses the activation of ZAK downstream signals in vitro and in vivo, while it is significantly less potent for the majority of 403 nonmutated kinases evaluated. Compound 3h also exhibits orally therapeutic effects on cardiac hypertrophy in a spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…ZAK is reported to inhibit human lung cancer cell growth via ERK and JNK activation in an AP‐1‐dependent manner . We additionally evaluated a compound as a selective ZAK inhibitor . Simultaneously, we also indicated that doxorubicin induces ZAK overexpression and consequently decreases cell viability while increases apoptosis in human OS cells .…”
Section: Introductionmentioning
confidence: 83%
“…ZAK is reported to inhibit human lung cancer cell growth via ERK and JNK activation in an AP‐1‐dependent manner . We additionally evaluated a compound as a selective ZAK inhibitor . Simultaneously, we also indicated that doxorubicin induces ZAK overexpression and consequently decreases cell viability while increases apoptosis in human OS cells .…”
Section: Introductionmentioning
confidence: 83%
“…Chemicals and inhibitors used were doxycycline (0.13 mg/mL), anisomycin (Standard: 1 mM, Low: 0.19 mM, High: 76 mM), cycloheximide (10 mM), lactimidomycin (1 mM), harringtonine (10 mM), emetine (Low: 1.8 mM, High: 360 mM), puromycin (10 mg/mL, added to cell culture medium 10 min before harvest) and sorbitol (500 mM), all from Sigma-Aldrich, except puromycin (BioNordika). Nilotinib (10 mM) was from Selleckchem and specific ZAK inhibitors YJZ and D28 were kind gifts from Xiaoyun Lu (Jinan University, China) (Chang et al, 2017). Ribotoxic enzymes and RNases for in vitro use were a-sarcin (10 mg/mL, Santa Cruz Biotechnology), and RNase T1 (2000 units/mL, 15 min at 37 C) and RNaseA (100 mg/mL, 15 min at 37 C), both from Life Technologies.…”
Section: Mouse Anti-actinmentioning
confidence: 99%
“…In order to theoretically calculate the binding mode, molecular docking studies have been carried out for the compound 6d against the cervical cancer suppressor gene 4 protein (PDB ID: 5X5O) 44 of the HeLa cervical cancer cell line using the Glide module of Schrodinger. The active compound 6d bounds very well with the cervical cancer protein 5X5O with a Glide score of −4.2, kcal mol −1 , which shows two crucial hydrogen bonding interactions with ASP92 through the NH substituent of the oxindole ring, SER89 with CO of the indole ring (Fig.…”
Section: In Silico Molecular Dockingmentioning
confidence: 99%